Synthesis of dibenzothiophenes via a deglucosylative C-H thiolation of biarylthioglycosides - Fatthalla, Maha; Jaballah, Oumayma B; Lotfi Efrit, Mohamed; Messaoudi, Samir (Synthesis)
The synthesis of dibenzothiophene derivatives through a deglucosylative C-H thiolation reaction is reported. This methodology enables products to be obtained in good yields under relatively mild operating conditions.